Proneural and neurogenic genes control specification and morphogenesis of stomatogastric nerve cell precursors in Drosophila. - Hartenstein, V.; Tepass, U.; Gruszynski-deFeo, E. (Developmental Biology, 1996)
The stomatogastric nervous system (SNS) of the Drosophila embryo develops from a placode which appears in the stomodeam epithelium. Most cells of this placode invaginate as three pouches (the iSNSPs) into the interior of the embryo. After separating from the stomodeum, the SNS pouches transiently form epithelial vesicles and eventually dissociate into solid clusters of cells which migrate on the foregut epithelium and differentiate into the neurons of the SNS. Prior and during iSNSP invagination, two small subpopulations of SNSPs (dSNSPs and tSNSPs) delaminate as individual cells from the SNS placode (Hartenstein et al., 1994). The results presented in this paper show that the neurogenic and proneural genes are expressed and required during all phases of SNS development to control the number, pattern, and structural characteristics of the SNSP subpopulations. First, loss-of-function mutations of the proneural and gain-of-function mutations of the neurogenic genes result in the absence or reduction of delaminating SNSPs; loss of function of neurogenic genes leads to the overproduction of d/tSNSPs and a loss of iSNSPs. Second, both proneural and neurogenic genes are involved in the invagination and dissociation of iSNSPs. Reduction of neurogenic gene function leads to a premature dissociation of iSNSPs; gain of neurogenic gene function blocks invagination and dissociation of these cells. Since all iSNSPs form a homogenous population with regard to their differentiative fate as SNS neurons, these results indicate that lateral inhibition is not a necessary aspect of the developmental process controlled by neurogenic and proneural gene function.